Cardiac Resynchronization Therapy and Atrial Fibrillation - Kamath, Ganesh S (J Atr Fibrillation, 2011)
Cardiac resynchronization therapy (CRT) is an important advance for the treatment of end--stage heart failure (HF). About 15–50% of HF is complicated by atrial fibrillation (AF) and associated with worsened outcomes. Meta-analyses from observational studies suggest that patients with AF derive similar benefits to CRT as patients in sinus rhythm (SR). The presence of AF, however, may interfere with optimal delivery of CRT due to competition with biventricular (BiV) capture by conducted beats. Atrioventricular junction (AVJ) ablation with permanent pacing eliminates interference by conducted beats and provides complete BiV capture. Catheter ablation of AF is an alternative to antiarrhythmic drugs to maintain sinus rhythm in patients with AF and HF. Randomized trial comparing catheter ablation, AVJ ablation and pharmacologic therapy are needed.